The Prevalensi Kejadian Stunting Pada Anak TK di Kabupaten Brebes - Istiklaili, Fifti (Indonesian Journal of Health Community, 2020)
Background: Stunting in children can affect him from childhood to adulthood. In the short term, stunting in children causes disruption in brain development, metabolism and physical growth. Methods: It was an observational research with crossectional study design. The population of this research is kindergarten children in Larangan and Jatibarang Districts. The research sample is kindergarten children who go to school in the Districts of Larangan and Jatibarang and are willing to become respondents. Primary data was collected by collecting data on anthropometric profiles (nutritional status) using scales of body weight and height. Result: The results of data analysis showed that the proportion of kindergarten children out of 111 children was 3.6% with the very short category and 17.1% in the short category, while 79.3% with the normal category. Conclusions: The prevalence of stunting in kindergarten children in Brebes is still high.